Implementation of Case-Based Learning to Enhance Students' Engagement and Academic Performance in Advanced Financial Accounting - Widowati, Amerti Irvin; Surjawati, Surjawati; TL, Dian Indriana (International Journal of Economics Development Research (IJEDR), 2025)
The learning paradigm shifts from teaching to learning, teaching to learning community. According to Permendikbud Number 3 of 2021, Key Performance Indicator (KPI) number 7 is to realize a collaborative and participatory classroom. The aim is to analyze the application of the case-based learning method to understanding advanced financial accounting and how to understand advanced financial accounting regarding the preparation of combined financial statements of head offices and branch offices. The object of this research is undergraduate Accounting students of the Faculty of Economics, University of Semarang, with a total of 6 classes. The subject of this research is Advanced Financial Accounting. The results showed that with this learning model system, lecturers will more easily provide a deep understanding to students. In this system, students act as the center of learning. It can increase student cognition and make them more active and innovative. Thus, this research can answer the question of whether the project-based learning model system with a case method approach can increase student creativity and innovation in understanding the Advanced Financial Accounting course, which is so complex.